Устойчивость по ограничениям векторных задач целочисленной оптимизации с выпуклыми квадратичными функциями ограничений - Семенова, Н.В. (Теорія оптимальних рішень, 2007)
The paper studies different types of stability taking place with respect to constraints as for vector integer optimization problems with convex quadratic constraints. Such problems consist in finding Paretoefficient solutions. The necessary and sufficient conditions for stability with respect to constraints are formulated. Some structural and topological properties of a space of input problem data are stated under which optimality of solutions.